A modified scaling law for 180° stripe domains in ferroic thin films - Zhao, G. P. (2011)
The periodicity of 180° stripe domains has been calculated analytically by assuming a linear change in magnetization/polarization in the domain wall. A modified scaling law was proposed between the domain period and the film thickness for ferroelectric and ferromagnetic thin films. Both the slope and intercept of this scaling line can be used to get domain wall thickness in a consistent manner, which enriches the understanding of domain walls. Theoretical results have been used to compare with recent experimental data and suggest a good agreement.